Efficacy of Combination Therapy with Linalool and Doxorubicin Encapsulated by Liposomes as a Two-in-One Hybrid Carrier System for Epithelial Ovarian Carcinoma - Wi TI (Dove Medical Press, 2020)
Tae In Wi,1,* Ji Eun Won,1,* Chan Mi Lee,1 Jeong-Won Lee,2 Tae Heung Kang,1 Byung Cheol Shin,3 Hee Dong Han,1 Yeong-Min Park1 1Department of Immunology, School of Medicine, Konkuk University, Chungju 380-701, South Korea; 2Department of Obstetrics and Gynecology, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, South Korea; 3Bio/Drug Discovery Division, Korea Research Institute of Chemical Technology, Daejeon, South Korea*These authors contributed equally to this workCorrespondence: Hee Dong Han; Yeong-Min ParkDepartment of Immunology, School of Medicine, Konkuk University, 268 Chungwondae-Ro, Chungju, Chungcheongbuk-Do 380-701, South KoreaTel +82-2-2030-7848; +82-2-2049-6330Fax +82-2-2049-6192Email hanhd@kku.ac.kr; immun3023@kku.ac.krBackground: Epithelial ovarian cancer (EOC) is a fatal gynecologic malignancy that is usually treated with chemotherapy after surgery. However, patients who receive chemotherapy experience severe side effects because of the inherent toxicity and high dose of chemotherapeutics. To overcome these issues, we suggest a combination therapeutic strategy using liposomes encapsulating linalool nanoemulsions (LN-NEs) and doxorubicin (DOX), a chemotherapeutic drug, to increase their synergistic antitumor efficacy and reduce the incidence of side effects from chemotherapeutics for EOC.Methods: The physical properties of LN-NE-DOX-liposomes were characterized by light scattering with a particle size analyzer. Cell viability was determined by MTT assay. Therapeutic efficacy was evaluated in a mouse HeyA8 EOC tumor model of ovarian carcinoma. Additionally, biochemical toxicity was analyzed for levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and blood urea nitrogen (BUN) using BALB/c nude mice.Results: The size of the liposomes encapsulating LN-NEs and DOX (LN-NE-DOX-liposomes) was 267.0 ± 4.6 nm, with a loading efficiency of 55.1 ± 3.1% and 27.2 ± 0.9% for linalool and DOX, respectively. Cell viability after treatment with LN-NE-DOX-liposomes was significantly decreased compared to that of cells treated with DOX liposomes, and apoptosis was significantly increased. Additionally, LN-NE-DOX-liposomes significantly inhibited HeyA8 EOC tumor growth compared to that of the control (p < 0.01) and DOX-liposome-treated groups (p < 0.05), while decreasing cell proliferation (Ki67) and microvessel density (CD31), and promoting apoptosis (caspase-3) compared to the control (p < 0.05). Moreover, the liposomal formulations induced no significant differences in biochemical toxicity (AST, ALT, and BUN) compared to healthy control mice, indicating that the liposomal formulations showed no overt toxicity in mice.Conclusion: This study demonstrates that the production of LN-NE-DOX-liposomes is a pivotal approach for EOC treatment, suggesting a novel combination therapeutic strategy.Keywords: linalool, liposome, ovarian carcinoma, doxorubicin, combination therapy